PENGARUH LATIHAN FEELING BALL TERHADAP PENINGKATAN KEMAMPUAN PUKULAN FOREHAND DALAM PERMAINAN TENIS MEJA PADA SISWA MAN 1 MEDAN - Samosir, Manami Aprianto; Siregar, Samsuddin; Hutasoit , Rido; Sihombing , Jesrin; Damanik, Sarto greos (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low forehand stroke ability of students in table tennis, characterized by lack of ball control, inaccuracy of stroke direction, and weak eye-hand coordination. This study aims to determine the effect of ball feeling training on improving forehand stroke ability in MAN 1 Medan students. The method used is an experiment with a one-group pretest-posttest design with a sample of 20 students selected through a purposive sampling technique. The research instrument is a forehand stroke ability test that covers aspects of accuracy, strength, and consistency. The results showed that the average pre-test score of 59.5 increased to 79.5 in the post-test with an increase of 20 points, and the results of the hypothesis test showed a calculated t value greater than the t table, indicating a significant effect. This finding is in line with the research of Alfarisi et al. (2022) which states that ball feeling training affects the accuracy of table tennis strokes, and is supported by the concept that ball control training has been shown to improve the accuracy and consistency of beginner players' strokes. Thus, feeling ball training is effective in improving ball control, motor coordination, consistency, and student confidence, making it an alternative method in physical education instruction